Auβ Quecksilber und Schwefel Rein: Johann Mathesius (1504-65) and Sulfur-Mercurius in the Silver Mines of Joachimstal - Norris, John A (Osiris, 2014)
The Sarepta, oder Bergpostill (1562) by Johann Mathesius is a book of sermons on mining and mineral subjects in which the composition and generation of metals in ore veins are discussed in terms of the sulfur-mercurius theory. Gur was an embodiment of mercurius or of sulfur and mercurius. Sulfur was evident in the sulfurous odor of the mines, in the supposed effects of subterranean heat, and in the deposition of mineral sulfur during the roasting of the ores. The toxic smoke given off during smelting was considered to be an additional manifestation of mercurius. Mathesius's sermons offer a glimpse of the ways miners' understanding of ores overlapped with alchemists' theories.
Keywords: Mercury; dějiny 16. století; Alchemy; síra; alchymie; History, 16th Century; Česká republika; Czech Republic; stříbro; hornictví; rtuť; Silver; Mining; Sulfur